2019
DOI: 10.1111/jcmm.14469
|View full text |Cite
|
Sign up to set email alerts
|

EIF2A promotes cell survival during paclitaxel treatment in vitro and in vivo

Abstract: The integrated stress response (ISR) is critical for cancer cell survival during stress stimuli and has been implicated in the resistance to cancer therapeutics, in which the mechanism, however, is poorly understood. Here, we showed that paclitaxel, the major chemotherapy drug for breast cancer, induced ISR and phosphorylated ser51 residue of EIF2S1 by EIF2AK3 and EIF2AK4. When exposed to paclitaxel, cancer cells activated the EIF2AK3/EIF2AK4‐pEIF2S1‐ATF4 axis and maintained redox homoeostasis by inducing expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…The authors showed that the loss of ISR increases paclitaxel-mediated cell death and that eIF2A is one of the key and essential factors for cancer cell survival under the conditions of paclitaxel-mediated ISR [102]. Knockdown of eIF2A substantially impaired cancer cell survival under the ISR [102]. The authors also found that elevated levels of eIF2A mRNA in patients with breast cancer are correlated with poor prognosis [102].…”
Section: Eif2a Function In Mammalian Systems In Non-aug Initiation Evmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors showed that the loss of ISR increases paclitaxel-mediated cell death and that eIF2A is one of the key and essential factors for cancer cell survival under the conditions of paclitaxel-mediated ISR [102]. Knockdown of eIF2A substantially impaired cancer cell survival under the ISR [102]. The authors also found that elevated levels of eIF2A mRNA in patients with breast cancer are correlated with poor prognosis [102].…”
Section: Eif2a Function In Mammalian Systems In Non-aug Initiation Evmentioning
confidence: 99%
“…Several additional recent reports have shown that eIF2A has specific functions during the ISR as well as cancer progression [102,103]. Chen et al demonstrated that eIF2A promotes cell survival during paclitaxel-mediated ISR in vitro and in vivo [102]. Paclitaxel is one of the major chemotherapy drugs for breast cancer treatment and its application is associated with strong ISR [102].…”
Section: Eif2a Function In Mammalian Systems In Non-aug Initiation Evmentioning
confidence: 99%
See 3 more Smart Citations